Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Karyawan pada Perumda Air Minum Tirta Hita Buleleng - Gebby Veralia Sandra; Made Dewanti (Penerbit Jurnal Indonesia, 2025)
This study investigates the influence of work motivation and work discipline on employee performance at Perumda Air Minum Tirta Hita Buleleng. The research aims to analyze both the simultaneous and partial effects of these variables. Employing a quantitative causal-comparative approach, data were collected from 107 permanent employees using a structured questionnaire. The instrument's validity and reliability were tested, and data analysis was conducted using multiple linear regression with SPSS 25.0, preceded by classical assumption tests. The results show that work motivation and discipline together significantly affect employee performance. However, work motivation has a negative and significant effect, while work discipline has a positive and significant effect on performance. The findings suggest that current motivational strategies may not align with employees' intrinsic needs, highlighting the need for more tailored approaches. The study concludes that enhancing discipline and revising motivation programs are crucial for improving employee performance.